The challenges of nuclear non-proliferation - Burns, Richard Dean; Coyle, Philip E. 1934- (Weapons of mass destruction series, 2015)
This exhaustive survey of the many aspects of nuclear non-proliferation efforts explains why some nations pursued nuclear programs while others abandoned them. It addresses key issues such as concerns over rogue states and stateless rogues, delivery systems made possible by technology, and the connection between nuclear weapons and ballistic missiles. It also examines whether non-proliferation regimes can deal with these threats or whether economic or military sanctions need to be developed and the feasibility of eliminating or greatly reducing the number of nuclear weapons